2019
DOI: 10.1155/2019/3512606
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Resin-Based Monoblock Endodontic Obturation System

Abstract: Objective The aim of the present study was to characterize a novel resin-based monoblock endodontic obturation system consisting of a polymeric cone and a resin-based endodontic sealer. Methods The preliminary tests performed for the experimental cone were as follows: cohesive strength, dimensional stability, standardization of the diameter and taper, calcium ion release, and radiopacity, for the characterization of the experimental sealer, film thickness and flow tests were performed. Tests were performed acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Also, many studies evaluated and compared the performance of obturation techniques; however, they have founded that no filling material or technique has fulfill ideal requirements. 6 These researches for an ideal root canal filling material has given rise to the concept of endodontic monoblocks. 2 Monoblock obturation concept obtained using single-cone technique associated with sealer, providing adhesion between the sealer and the dentinal tubules and also, between the sealer and the obturating cones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, many studies evaluated and compared the performance of obturation techniques; however, they have founded that no filling material or technique has fulfill ideal requirements. 6 These researches for an ideal root canal filling material has given rise to the concept of endodontic monoblocks. 2 Monoblock obturation concept obtained using single-cone technique associated with sealer, providing adhesion between the sealer and the dentinal tubules and also, between the sealer and the obturating cones.…”
Section: Introductionmentioning
confidence: 99%
“…2 Monoblock obturation concept obtained using single-cone technique associated with sealer, providing adhesion between the sealer and the dentinal tubules and also, between the sealer and the obturating cones. 6 However, the main purpose of adhesive root canal filling materials is the formation of fluid tight seal via creation of monoblock which provides strengthening to endodontically treated tooth. 7 Some laboratory studies have shown that creation of monoblock root filling is a real challenge because of the heterogeneous composition of root dentin and it complex anatomy like fins, extensions and isthmuses; presence of sclerotic dentin in the apical third; and accumulation of large amount of hard tissue debris within the canal space.…”
Section: Introductionmentioning
confidence: 99%